THE TALISMAN - La Plante, Lynda (London : Simon & Schuster, 2019)
In this meticulous and absorbing account, Ford reviews the latest scientific evidence to show that the popular accounts of dinosaurs' lives contain ideas that are no more than convenient inventions: how dinosaurs mated, how they hunted and communicated, how they nursed their young, even how they moved. He uncovers many surprising details which challenge our most deeply-held beliefs - such as the revelation that an asteroid impact did not end the dinosaurs' existence.
The big lie -- You ain't no ballerina -- The kid with the big shekels -- Pele -- Buy, lie, and cry -- The great muckle gype -- Tacky is as tacky does -- Your day in Trumpland -- Mo Trump mo problems -- One good punch -- Trump v. Obama -- Professional pest -- Ewwwww -- Who's your caddies? -- Little ball, big ball -- The stain.
Originally published: London: Sidgwick & Jackson, 1987.
Includes bibliographical references and index.
Keywords: Inheritance and succession -- Fiction; Domestic fiction